K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 3 2022

undefined

25 tháng 3 2022

Thanks

7 tháng 8 2021

a) \(\dfrac{x.2}{-15}=\dfrac{-5}{3}\)

\(\dfrac{x.2}{-15}=\dfrac{25}{-15}\)

x.2=25

x=12,5

b) \(\dfrac{x-1}{-12}=\dfrac{-3}{x-1}\)

(x-1)2=-3.(-12)

(x-1)2=36 

⇒(x-1)2\(\Rightarrow\left[{}\begin{matrix}x-1=6\\x-1=-6\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=7\\x=-5\end{matrix}\right.\)

 

27 tháng 1 2023

\(a,\left(x-\dfrac{1}{2}\right):\dfrac{1}{3}+\dfrac{5}{7}=9\dfrac{5}{7}\)

\(\Leftrightarrow\left(x-\dfrac{1}{2}\right).3=\dfrac{68}{7}-\dfrac{5}{7}\)

\(\Leftrightarrow\left(x-\dfrac{1}{2}\right).3=9\)

\(\Leftrightarrow x-\dfrac{1}{3}=3\)

\(\Leftrightarrow x=3+\dfrac{1}{3}\)

\(\Leftrightarrow x=\dfrac{9}{3}+\dfrac{1}{3}\)

\(\Leftrightarrow x=\dfrac{10}{3}\)

\(b,x+30\%x=-1,31\)

\(\Leftrightarrow x+\dfrac{3}{10}.x=-\dfrac{131}{100}\)

\(\Leftrightarrow x.\left(1+\dfrac{3}{10}\right)=-\dfrac{131}{100}\)

\(\Leftrightarrow x.\dfrac{13}{10}=-\dfrac{131}{100}\)

\(\Leftrightarrow x=-\dfrac{131}{100}.\dfrac{10}{13}\)

\(\Leftrightarrow x=-\dfrac{131}{130}\)

\(c,-\dfrac{2}{3}x+\dfrac{1}{5}=\dfrac{1}{10}\)

\(\Leftrightarrow\dfrac{-2}{3}x=\dfrac{1}{10}-\dfrac{1}{5}\)

\(\Leftrightarrow\dfrac{-2}{3}x=\dfrac{1}{10}-\dfrac{2}{10}\)

\(\Leftrightarrow-\dfrac{2}{3}x=-\dfrac{1}{10}\)

\(\Leftrightarrow x=-\dfrac{1}{10}.\left(-\dfrac{3}{2}\right)\)

\(\Leftrightarrow x=\dfrac{3}{20}\)

a) Ta có: \(\left(2x-1\right)\left(x^2-x+1\right)=2x^3-3x^2+2\)

\(\Leftrightarrow2x^3-2x^2+2x-x^2+x-1-2x^3+3x^2-2=0\)

\(\Leftrightarrow3x=3\)

hay x=1

Vậy: S={1}

b) Ta có: \(\left(x+1\right)\left(x^2+2x+4\right)-x^3-3x^2+16=0\)

\(\Leftrightarrow x^3+2x^2+4x+x^2+2x+4-x^3-3x^2+16=0\)

\(\Leftrightarrow6x=-20\)

hay \(x=-\dfrac{10}{3}\)

c) Ta có: \(\left(x+1\right)\cdot\left(x+2\right)\left(x+5\right)-x^3-8x^2=27\)

\(\Leftrightarrow\left(x^2+3x+2\right)\left(x+5\right)-x^3-8x^2-27=0\)

\(\Leftrightarrow x^3+5x^2+3x^2+15x+2x+10-x^3-8x^2-27=0\)

\(\Leftrightarrow17x=17\)

hay x=1

4 tháng 9 2021

a)x.(5-2x)-2x.(1-x)=15
   x [ 5 - 2x -2.(1-x) ] = 15
   x ( 5 - 2x -2 + 2x ) =15
   x . 3 =15
   x = 5
b)(3x+2)2+(1+3x).(1-3x)=2
   9x2+12x+4+1-9x2=2
   12x + 5 = 2
    12x = -3
        x = -1/4

4 tháng 9 2021

a)\(\Leftrightarrow\)\(5x-2x^2-2x+2x^2=15\)

\(\Leftrightarrow\)\(3x=15\)

\(\Leftrightarrow\)\(x=5\)

b)\(\Leftrightarrow\)\(9x^2+12x+4+1-9x^2-2=0\)

\(\Leftrightarrow\)\(12x+3=0\)

\(\Leftrightarrow\)\(x=-0,25\)

21 tháng 4 2022

a) 2 + 1/3 - x = 1 + 1/4

7/3 -x = 5/4

x = 7/3 - 5/4

x = 13/12


b) (2/7 x 2) : x = 1 :7/2 

4/7 : x = 2/7

x = 4/7 : 2/7

x = 2

21 tháng 4 2022

a) 2 + 1/3 - x = 1 + 1/4

           7/3 -x = 5/4

                  x = 7/3 - 5/4

                  x = 13/12


b) (2/7 x 2) : x = 1 :7/2 

          4/7 : x = 2/7

                  x = 4/7 : 2/7

                  x = 2

a) Ta có: \(\left(2x-3\right)-\left(x-5\right)=\left(x+2\right)-\left(x-1\right)\)

\(\Leftrightarrow2x-3-x+5=x+2-x+1\)

\(\Leftrightarrow x+2=3\)

hay x=1

Vậy: x=1

b) Ta có: \(2\left(x-1\right)-5\left(x+2\right)=-10\)

\(\Leftrightarrow2x-2-5x-10=-10\)

\(\Leftrightarrow-3x=-10+10+2=2\)

hay \(x=-\dfrac{2}{3}\)

Vậy: \(x=-\dfrac{2}{3}\)

18 tháng 5 2021

a, (2x - 3) - (x - 5) = (x + 2) - (x - 1)

 2x - 3 - x + 5 = x + 2 - x + 1

(2x - x) + (-3 + 5) = (x - x) + (2 + 1)

x + 2 = 3

x = 1

22 tháng 12 2022

a.\(\dfrac{1}{3}\) + x  = \(\dfrac{5}{6}\)

       x = \(\dfrac{5}{6}\) - \(\dfrac{1}{3}\)

      x = \(\dfrac{1}{2}\)

b. | x-1| - \(\dfrac{2}{5}\) = \(\dfrac{11}{10}\) 

   | x-1|        = \(\dfrac{11}{10}\) + \(\dfrac{2}{5}\)

  |x-1|        = \(\dfrac{3}{2}\)

\(\left[{}\begin{matrix}x-1=\dfrac{3}{2}\\x-1=-\dfrac{3}{2}\end{matrix}\right.\)

\(\left[{}\begin{matrix}x=\dfrac{3}{2}+1\\x=-\dfrac{3}{2}+1\end{matrix}\right.\)

\(\left[{}\begin{matrix}x=\dfrac{5}{2}\\x=-\dfrac{1}{2}\end{matrix}\right.\)

 

c, \(\dfrac{1}{3}\) + \(\dfrac{2}{3}\) ( \(\dfrac{x}{2}\) + 3) = 1

            \(\dfrac{2}{3}\) (\(\dfrac{x}{2}\) + 3) = 1 - \(\dfrac{1}{3}\)

             \(\dfrac{2}{3}\) ( \(\dfrac{x}{2}\) + 3) = \(\dfrac{2}{3}\)

                   \(\dfrac{x}{2}\) + 3 = 1

                   \(\dfrac{x}{2}\)       = 1 - 3

                    \(\dfrac{x}{2}\)    = -2

                     \(x\) = -4

d, \(\dfrac{x+2}{3}\) = \(\dfrac{27}{x+2}\)

(x+2)2 = 27.3

(x+2) =92

\(\left[{}\begin{matrix}x+2=9\\x+2=-9\end{matrix}\right.\)

\(\left[{}\begin{matrix}x=7\\x=-11\end{matrix}\right.\)